Asherah and figurines : how the worship of a goddess affected the activites of women in Iron Age II Megiddo - Lingenfelter, Hannah (My University, 2013)
The Israelites' religious history is easily found documented in the Hebrew Bible. Certain aspects of their religion, though, have been expanded upon by the use of archaeology, especially looking at the idea of popular religion versus state religion. This study focused on the cultic worship of the goddess, Asherah, in the city of Megiddo, during the Iron Age II period. Both the religious cult and gendered spaces were analyzed in order to evaluate the extent that the state religion was involved in cultic worship, as well as to understand how women's economic and social activities were affected by the worship of Asherah. The information may then add to our understanding of the ancient Israelite's internal religious debate over what was deemed orthodox and it will further other studies about women's important economic roles in patriarchal societies.
Keywords: Megiddo (Extinct city); Middle East--Antiquities.; Asherahs (Jewish liturgical objects)